Transplantation of a single kidney from pediatric donors less than 10 kg to children with poor access to transplantation: a two-year outcome analysis - Su, Xiaojun (BMC Nephrol, 2020)
BACKGROUND: Access to kidney transplantation by uremic children is very limited due to the lack of donors in many countries. We sought to explore small pediatric kidney donors as a strategy to provide transplant opportunities for uremic children. METHODS: A total of 56 cases of single pediatric kidney transplantation and 26 cases of en bloc kidney transplantation from pediatric donors with body weight (BW) less than 10 kg were performed in two transplant centers in China and the transplant outcomes were retrospectively analyzed. RESULTS: The 1-year and 2-year death-censored graft survival in the en bloc kidney transplantation (KTx) group was inferior to that in the single KTx group. Subgroup analysis of the single KTx group found that the 1-year and 2-year death-censored graft survival in the group where the donor BW was between 5 and 10 kg was 97.7 and 90.0%, respectively. However, graft survival was significantly decreased when donor BW was ≤5 kg (p < 0.01), mainly because of the higher rate of thrombosis (p = 0.035). In the single KTx group, the graft length was increased from 6.7 cm at day 7 to 10.5 cm at 36 months posttransplant. The estimated glomerular filtration rate increased up to 24 months posttransplant. Delayed graft function and urethral complications were more common in the group with BW was ≤5 kg. CONCLUSIONS: Our study suggests that single kidney transplantation from donors weighing over 5 kg to pediatric recipients is a feasible option for children with poor access to transplantation.